2017
DOI: 10.1080/02699052.2017.1380843
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of post-concussive and depressive symptoms in adolescents with prolonged recovery from concussion

Abstract: Primary Objective: To investigate the symptom trajectories of depressive and post-concussive symptoms (PCS) in slow-to-recover adolescents to understand how the two sets of symptoms are related. Research Design: We used data from a randomized clinical trial of a collaborative care intervention for post-concussive symptoms to better understand how these two sets of symptoms change in parallel over six months. Methods and Procedure: PCS and depressive symptom scores for 49 adolescents (ages 11–17) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In particular, the relationship between symptom experience and psychosocial symptoms including depression have been explored. Several studies have explored the symptom experience of concussed adolescents who are slow to recover from concussion (Brooks et al, 2019; Durish et al, 2019; Stein et al, 2017). Stein et al (2017) explored symptom trajectories of depression and post‐concussive symptoms in adolescents aged 11–17 who were deemed slow to recover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the relationship between symptom experience and psychosocial symptoms including depression have been explored. Several studies have explored the symptom experience of concussed adolescents who are slow to recover from concussion (Brooks et al, 2019; Durish et al, 2019; Stein et al, 2017). Stein et al (2017) explored symptom trajectories of depression and post‐concussive symptoms in adolescents aged 11–17 who were deemed slow to recover.…”
Section: Discussionmentioning
confidence: 99%
“…Both post‐concussive symptoms and depressive symptoms based on the Patient Health Questionnaire (PHQ‐9) decreased over the course of 6 months. The authors noted that higher post‐concussive symptom scores at enrollment predicted a higher depression scores over the study period (Stein et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown an increased risk of anxiety and depressive symptoms following concussion (Hawley, Ward, Magnay, & Long, 2004;Luis & Mittenberg, 2002), suggesting that increased PCS may lead to greater anxiety/ depressive symptomatology rather than the converse. Given the overlap that exists between depression and anxiety, and many PCS (e.g., fatigue), changes in one may affect changes in the other in a bidirectional manner (see Stein et al, 2017). More research is needed to examine the causal relationships among these variables.…”
Section: Discussionmentioning
confidence: 99%
“…delayed recovery, 105 further demonstrating mental health as an important target for intervention. Since the majority of children and adolescents with clinical mental health difficulties do not access recommended care, 106 incorporating mental health risk into post-injury management represents an avenue to engage young people with mental health services to either prevent unnecessary problems emerging or to treat premorbid issues.…”
Section: Reviewmentioning
confidence: 99%